2018
DOI: 10.17576/jkmjc-2018-3402-14
|View full text |Cite
|
Sign up to set email alerts
|

Satira Politik: Analisis Internet Trolling di Malaysia (Political Satire: Analysis on the Internet Trolling in Malaysia)

Abstract: Satira politik merupakan satu bentuk komunikasi politik terdiri daripada pelbagai jenis. Satira politik melalui pendekatan Internet trolling pula dilihat semakin berkembang di Malaysia. Internet trolling boleh didapati dalam bentuk gambar (memes) atau rakaman (video) dan merupakan salah satu medium yang menarik digunakan dalam media sosial sebagai alat menyampaikan maklumat. Fenomena ini telah menular dalam kebanyakan aplikasi media sosial. Internet trolling seringkali digunakan terhadap para pemimpin politik … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…But what is anticipated is that political parties and social media users would be more responsible, mature, and constructive while posting or sharing any material politics to avoid any unintended effects that could undermine the country's stability and unity (Afi Roshezry Abu Bakar & Mohd Azmir Mohd Nizah, 2021). With the growth of social media use in a very widespread manner, political satire (memes) and Internet trolling have emerged as the next forms of communication (Raja Zulkifi et al, 2018).…”
Section: Memes As Political Marketing Strategymentioning
confidence: 99%
“…But what is anticipated is that political parties and social media users would be more responsible, mature, and constructive while posting or sharing any material politics to avoid any unintended effects that could undermine the country's stability and unity (Afi Roshezry Abu Bakar & Mohd Azmir Mohd Nizah, 2021). With the growth of social media use in a very widespread manner, political satire (memes) and Internet trolling have emerged as the next forms of communication (Raja Zulkifi et al, 2018).…”
Section: Memes As Political Marketing Strategymentioning
confidence: 99%
“…Technological modernization is seen as a new dimension for humans to explore the real world without borders. Based on the statement of Raja et al (2018), the dependence of Malaysians on the use of Google websites to obtain information is very high, this includes participation in other social media platforms. Looking at the context of the use of social media and sources of political information, social media is becoming increasingly popular among people in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A survey from Masyarakat Telekomunikasi Indonesia found that unfiltered news could harm the stability of the Indonesian community (MASTEL, 2017), as it could trigger insecurity among citizens and even affect the political agenda (Salman et al, 2016). Certainly, we could not deny the benefit of having good social media as a control to the administration (Raja Zulkifi, Mohd Sani, Muhamad, & Ahmad, 2018). This provided a basis for the following hypothesis:…”
Section: The Tendency To Spread Newsmentioning
confidence: 99%